A survey of public bookmobile services in Luzon - Baker, Elaine C.; Vallejo, Rosa M.; David, Conrado D. (Quezon City : Institute of Library Science, University of the Philippines Diliman, 1978)
This study is a survey of the six bookmobiles which provide public service now operating in Luzon: the Tarlac bookmobile, the privately-owned bookmobile sponsored by the Social Communications Center and S.C. Johnson and Son, Inc., the Makati bookmobile, the Batangas bookmobile, the jointly-sponsored Learning Mobile which takes films and books to schools in Baguio City and Benguet Province, and the Quezon bookmobile.
Profiles of the six bookmobiles reveal that great variety exists among them, the only common denominator being that they all are primarily focused on providing school library service.
While all the six bookmobiles are to a degree meeting their objectives, that is, to reach and serve as many people as possible where a permanent library is not established, some are limited in their effectiveness. The major factors which seem to hinder effective bookmobile service are inadequate collections, too large or too small a vehicle, and insufficient funds for operating expenses. To a lesser degree inefficient procedures and scheduling arrangements are also impeding service.
The study also indicates that cost effectiveness is not being realized in most bookmobile operations, primarily because of the low rate of the circulation of materials.
As of now, public enthusiasm for bookmobile service is high, and the users who were polled in the study registered general satisfaction with the services they are receiving. School personnel also generally revealed position attitudes toward bookmobile programs, citing as their principal advantage that they stimulate students' interest in reading.
While investigation into the impact of bookmobile service is inconclusive, there is some evidence that such service does increase reading, as shown by the findings that Makati sixth grade students who have experienced bookmobile service for two years apparently read three to four more books per student last year than did fourth-year high school students in Tarlac Province who are just beginning to receive bookmobile service.
It is concluded that while all the bookmobiles in Luzon are augmenting existing library facilities, there are many ways in which both services and cost effectiveness of nearly all programs could be improved. It is also indicated that no new bookmobiles should be fielded unless the sponsoring agency stands ready and willing to provide all the elements needed to ensure a successful bookmobile program.
Mimeographed.
Vita.
Thesis (Master of Library Science)--University of the Philippines Diliman
Keywords: Bookmobiles--Philippines--Luzon.; Libraries, Traveling--Philippines--Luzon.